Impulsive Action and Impulsive Choice Are Differentially Expressed in Rats Depending on the Age at Exposure to a Gambling Task - Cho, Bo Ram; Kwak, Myung Ji; Kim, Wha Young; Kim, Jeong-Hoon (Frontiers in Psychiatry, 2018)
Impulsivity is considered an important feature associated with the development of numerous psychiatric disorders, including addictions. In the behavioral approach, impulsivity can be broadly divided into two distinct subtypes: impulsive action and choice. In the present study, we used a rodent version of the gambling task (rGT) to examine how impulsive action and impulsive choice are differentially influenced by difference in age at exposure (i.e., late adolescents/young adults versus mature adults) to rGT. Rats were trained in a touch-screen chamber to learn the relationships between 4 light signals on the window of the screen and accompanying reward outcomes or punishments associated with different magnitudes and probabilities. Depending on their stabilized pattern of preference when allowed free choice, rats were categorized into risk-averse or risk-seeking group. While undergoing a series of experimental schemes, including extinction, re-acquisition, and acute cocaine injection, rats were re-tested for their premature response during inter-trial interval and choice preference toward the 4 different windows in rGT. Notably, rats exposed early, compared with those exposed late, to rGT showed increased impulsive action, particularly during re-acquisition period, in all sub-groups. In contrast, rats exposed late, compared with those exposed early, to rGT showed increased impulsive choice after acute cocaine injection, but these results were only obtained in a sub-group pre-categorized as high impulsive and risk-averse. These results suggest that different aspects of impulsivity can be differentially expressed during decision-making, and differentially influenced by the age at exposure to a gambling task.